2003
DOI: 10.1007/bf02660775
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of early closure of loop ileostomies

Abstract: Closure of a loop ileostomy early after the initial operation was feasible in 18 of 27 patients and was associated with low morbidity and no mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 27 publications
1
61
1
1
Order By: Relevance
“…Stoma-related complications presented during the whole period the stoma was in place. Therefore, many of the encountered complications could have been avoided if the ileostomy had been closed earlier after its construction, for example during the same hospital admission [26]. An uncomplicated recovery after the initial operation and the absence of anastomotic leakage as radiologically tested by water-soluble contrast enema examination are of course crucial prerequisites for this early closure.…”
Section: Discussionmentioning
confidence: 99%
“…Stoma-related complications presented during the whole period the stoma was in place. Therefore, many of the encountered complications could have been avoided if the ileostomy had been closed earlier after its construction, for example during the same hospital admission [26]. An uncomplicated recovery after the initial operation and the absence of anastomotic leakage as radiologically tested by water-soluble contrast enema examination are of course crucial prerequisites for this early closure.…”
Section: Discussionmentioning
confidence: 99%
“…Early closure (EC) of the temporary loop ileostomy might reduce both stoma-related morbidity and patient discomfort. Two prospective non-randomized studies including 27 and 39 patients respectively 12,13 have evaluated the feasibility of EC of the temporary loop ileostomy after rectal surgery. These two pilot studies reported encouraging results, with no deaths and no need for revisional procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Perez et al [10] reported a higher rate of postoperative complications in patients operated earlier than 8.5 weeks after the primary surgery and concluded that the time interval should not be shorter. Bakx et al [22], however, showed that loop ileostomy closure is possible as early as 7–21 days after its construction in selected patients. Mansfield et al [23] reported more postoperative complications in patients with a shorter interval to ileostomy closure, whereas Hallböök et al [24] did not find any differences.…”
Section: Discussionmentioning
confidence: 99%